Controlled density thermoplastic multilayer film
Patent Information
- Application Number
- JP2022507401
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-05
- Filing Date
- 2020-08-05
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-08-05
Smart Images

Figure 0007610577000005 
Figure 0007610577000006 
Figure 0007610577000007
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Patent Application No. 62 / 882,821, filed August 5, 2019, the entire disclosure of which is incorporated herein by reference. [Background technology]
[0002] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to biaxially oriented multilayer films, and more specifically, to biaxially oriented multilayer films that exhibit lower density and improved transparency.
[0003] Thermoplastic film-like materials are well known in the art. Such materials are commonly used in flexible packaging, solar control window films, construction of substrates for electronics manufacturing, and many other important and valuable applications. Manufacturers have aggressively pursued the production of these plastic materials in substantial profitable quantities due to the performance and cost advantages offered by the technology.
[0004] The polymers and resins used to produce such film-like materials can be obtained from many commercial sources, for example, from the conversion of petroleum sources, such as in the case of polyester, nylon, and polycarbonate materials, from the conversion of natural gas sources, such as in the case of polyethylene, polypropylene, butadiene, and other materials, and through natural processes, such as in the case of carbohydrate polymers such as cellulose derivatives, starch derivatives, polylactic acid, and polyethylene furonates. Additionally, a combination of material sources is also used to produce thermoplastic resin materials as a methodology to balance cost and supply issues.
[0005] Producing films with various desired properties is highly dependent on the type of material used to produce the thermoplastic film as well as the processing techniques. The properties of thermoplastic materials for films can be modified by modifying the casting and stretching processes. These modifications are commonly available in state-of-the-art continuous biaxial orientation lines, blown film lines, molding and sheet extrusion lines. In the case of thermoplastic materials such as polypropylene or polyethylene, low density, low crystalline film-like materials can be made at low extrusion and stretching conditions. Such materials are easily heat fused to other materials. However, high stretch ratios greatly increase the crystallinity of the materials, resulting in improved heat resistance, barrier properties, and solvent resistance of these same materials. It is well known in the art to vary processing temperatures, stretch ratios, heat setting conditions, processing speeds, and other machine-related processes to achieve desired end-use properties.
[0006] Density is a well-described property of polymeric materials and blends. Cavitation or blending with miscible materials with lower bulk density can be used to reduce the density of thermoplastic film-like materials. In the case of highly oriented films, cavitation can reduce the density of the film. Density reduction is desired for many reasons, such as using less material to create a material of equivalent thickness, thus potentially reducing costs. Furthermore, microvoiding or cavitation can produce materials with high opacity. In addition, using less material is a desirable goal for lightweight packaging structures due to potential environmental benefits.
[0007] For the production of low density, highly transparent thermoplastic film materials, the only practical solution currently available is to rely on resins that are inherently low density. For example, PET film can often be replaced with biaxially oriented nylon (BON) film. Nylon resins, which are inherently less dense than PET resins, produce materials with higher yields, or greater surface area per unit of mass, at comparable thicknesses. However, other attributes of the PET film-like material, such as barrier properties and heat resistance, may need to be sacrificed in order to take advantage of the lower density BON material.
[0008] Although clear film materials exist, and low density film materials exist, there remains a continuing need for film materials that have reduced density without reducing transparency. Summary of the Invention
[0009] The present disclosure relates to a biaxially oriented multilayer film. A biaxially oriented multilayer film is a stack of n layer units A-B (A-B) n where n is 32 or greater and each layer unit A-B has individual layers including a first layer A and a second layer B overlying the first layer A. The biaxially oriented multilayer film includes an intralayer void within a portion of the individual layers in the stack. The intralayer void has a width to height aspect ratio of 20:1 to 500:1. The first layer of the layer unit has a first composition and the second layer of the layer unit has a second composition. The first composition includes a first thermoplastic and a first polymer that is immiscible with the first thermoplastic. The second composition includes a second thermoplastic that may be the same as the first thermoplastic or different from the first thermoplastic. [Brief description of the drawings]
[0010] [Figure 1] 1 is an exemplary embodiment of a stack according to one or more embodiments of the present disclosure. [Diagram 2] 1 is an exemplary embodiment of a unit according to one or more embodiments of the present disclosure. [Diagram 3] 1 is a cross-sectional SEM micrograph of a multilayer film according to one embodiment of the present disclosure. [Figure 4] 4 is a cross-sectional SEM micrograph of the multilayer film of FIG. 3. [Diagram 5] FIG. 2 is a schematic diagram of intralayer voids present in a multilayer film according to an embodiment of the present disclosure. [Figure 6] 1 is a SEM micrograph of a multilayer film produced as a comparative example to a multilayer film according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The embodiments of the present disclosure include a biaxially oriented multilayer film. A biaxially oriented multilayer film is a stack of n layer units A-B (A-B) n where n is 32 or greater and each layer unit A-B has individual layers including a first layer A and a second layer B overlying the first layer A. The biaxially oriented multilayer film includes an intralayer void within a portion of the individual layers in the stack. The intralayer void has a width to height aspect ratio of 20:1 to 500:1. The first layer of the layer unit has a first composition, the first composition including a first thermoplastic and a first polymer immiscible with the first thermoplastic. The second layer of the layer unit has a second composition, the second composition including a second thermoplastic. The second thermoplastic may be the same as or different from the first thermoplastic.
[0012] In various embodiments, the biaxially oriented multilayer film is a stack of n layer units A-B (A-B) nwhere n is 32 or greater and each layer unit A-B has individual layers including a first layer A and a second layer B overlying the first layer A. The biaxially oriented multilayer film includes intralayer voids within some of the individual layers in the stack. The intralayer voids have a width-to-height aspect ratio of 20:1 to 500:1. The first layer of the layer unit has a first composition and the second layer of the layer unit has a second composition. The first composition includes a first thermoplastic and a void former. The void former creates voids in the first thermoplastic. It is understood that there are a variety of void formers that may be suitable for creating voids in the first thermoplastic. The second composition includes a second thermoplastic that may be the same as the first thermoplastic or different from the first thermoplastic.
[0013] The term "comprising" is used in the specification and claims as an open-ended term that does not exclude other unspecified elements. Unless specifically stated otherwise, the terms "including" and "having" are synonymous with "comprising."
[0014] As used in the specification and the appended claims, singular nouns preceded by the articles "a," "an," or "the" are to be understood to include the plural unless the context clearly indicates otherwise.
[0015] In an embodiment, the multilayer film comprises a stack. Figure 1 illustrates the stack. The stack 100 comprises a plurality of units 120. Figure 2 illustrates the units 120. Each unit 120 comprises a first layer 121 and a second layer 122.
[0016] In one or more embodiments, the first layer comprises a first thermoplastic material. In various embodiments, the second layer comprises a second thermoplastic material.
[0017] In one or more embodiments, the first thermoplastic and the second thermoplastic may be selected from homopolymers, copolymers, terpolymers of C2 to C8 α-olefins, polyamides, polyacetates, polyesters, polycarbonates, polystyrenes, poly(vinyl chloride), poly(ethylene vinyl alcohol), poly(vinyl alcohol), poly(ethylene vinyl acetate), poly(acrylic acid), and poly(ethylene terephthalate), or any blend or mixture of the foregoing materials. In some embodiments, the first thermoplastic, the second thermoplastic, or both, are polypropylene-based homopolymers or copolymers. In other embodiments, the first thermoplastic, the second thermoplastic, or both, are polyethylene-based homopolymers or copolymers (e.g., LLDPE).
[0018] In various embodiments, the first thermoplastic may include polyethylene terephthalate (PET). In some embodiments, the second thermoplastic may include PET, and in one or more embodiments, the first thermoplastic and the second thermoplastic may include PET.
[0019] In some embodiments, the first thermoplastic comprises polybutylene terephthalate (PBT), in some embodiments, the second thermoplastic comprises PBT, and in one or more embodiments, both the first thermoplastic and the second thermoplastic comprise PBT.
[0020] In some embodiments, the first thermoplastic comprises PET and the second thermoplastic comprises PBT.
[0021] In embodiments of the biaxially oriented multilayer film, the first composition further comprises a first polymer immiscible with the first thermoplastic. In some embodiments, the second composition may further comprise a second polymer immiscible with the second thermoplastic, the second polymer being the same or different than the first polymer. The first polymer may be selected from polymers having a density lower than that of the first thermoplastic. The second polymer, if present, may be selected from polymers having a density lower than that of the second thermoplastic.
[0022] In one or more embodiments of the biaxially oriented multilayer film, the first polymer may include one or more cycloolefin polymers. The cycloolefin polymer may be a homopolymer or copolymer that includes polymerized cycloolefin units and, optionally, acyclic olefin comonomers. Suitable cycloolefin polymers include 0.1% to 100% by weight of cycloolefin units, or 10% to 99% by weight of cycloolefin units, or 50% to 95% by weight of cycloolefin units, respectively, based on the total weight of the cycloolefin polymer. In some embodiments, the cycloolefin polymer may have a structure according to any one of the following formulas (I), (II), (III), (IV), (V), or (VI).
[0023] [ka]
[0024] In formula (I), (II), (III), (IV), (V) or (VI), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are the same or different and are independently a hydrogen atom or (C 30) hydrocarbyl. The term "hydrocarbyl" refers to a hydrocarbon radical. Optionally, the radical R 1 From R 8 Any two or more of may be periodically linked to each other. 30 Examples of hydrocarbyl radicals include linear or branched (C1-C8) alkyl, (C6-C 18 )Aryl, (C7-C 20 ) alkylene aryl, and (C3-C 20 ) cycloalkyl. The term "alkyl" refers to a branched or unbranched alkane radical. The term "aryl" refers to an aromatic ring structure having radicals on carbon atoms of the aromatic ring. The term "alkylenearyl" refers to an alkyl aromatic structure having radicals on carbons of an alkyl group.
[0025] The cycloolefin polymer may contain from 0 to 45 weight percent polymerized units of at least one monocyclic olefin of formula (VII), based on the total weight of the cycloolefin polymer.
[0026] [ka]
[0027] In formula (VII), n is an integer from 3 to 10.
[0028] The cycloolefin polymer may further comprise from 0% to 99% by weight polymerized units of an acyclic olefin of Formula (VIII), based on the total weight of the cycloolefin polymer.
[0029] [ka]
[0030] In formula (VIII), R 9 , R 10 , R 11 , and R 12is a hydrogen atom (-H), (C1-C 10 ) hydrocarbyl, (C1-C8) alkyl, or (C6-C 14 ) aryl.
[0031] Also suitable in principle are cycloolefin polymers which are obtainable by ring-opening polymerization of at least one of the monomers of the formulae (I) to (VI) and subsequent hydrogenation.
[0032] Cycloolefin homopolymers are synthesized from monomers of any one of formulas (I) to (VI).
[0033] The proportion of polymerized units of acyclic olefin of formula (VIII) is up to 99 wt%, 5 wt% to 80 wt%, or 10 wt% to 60 wt%, based on the total weight of the respective cycloolefin copolymer.
[0034] In various embodiments, the cycloolefin copolymer (COC) comprises polymerized units of a polycyclic olefin of formula (VIII), where R 9 , R 10 , R 11 , and R 12 is a cyclohydrocarbyl having a norbornene parent structure of formula (I). In some embodiments, the COC comprises polymerized units of norbornene or tetracyclododecene of formula (III), where R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , and R 7 is hydrogen.
[0035] In other embodiments, the first polymer comprises a COC that includes polymerized units of an acyclic olefin such as ethylene. In some embodiments, the first polymer comprises a copolymer of norbornene / ethylene and tetracyclododecene / ethylene that includes from 5 wt% to 80 wt% ethylene units, or from 10 wt% to 60 wt% ethylene units, based on the weight of the copolymer.
[0036] COCs may include compounds produced by heterogeneous or homogeneous catalysis with organometallic compounds according to any known synthetic route. Suitable catalytic systems based on the cocatalysis of titanium and / or vanadium compounds in combination with aluminum organyls.
[0037] The cycloolefin copolymer can be incorporated into the biaxially oriented multilayer film as starting material either in the form of granules or granulated concentrate, as is well known in the art. The polyester granules, and any further components, are premixed for this purpose, and the mixture is then fed into an extruder. In the extruder, the components are further mixed and heated to a processing temperature. With respect to the manufacturing process of the present invention, it is advantageous for the extrusion temperature to be sufficiently higher than the glass transition temperature Tg of the cycloolefin copolymer (COC), i.e., generally at least 30°C, 40°C to 230°C, or 50°C to 200°C higher than the glass transition temperature of the cycloolefin copolymer (COC).
[0038] In various embodiments, the first composition comprises 0.5% to 10% by weight of the first polymer, based on the total weight of the first composition. In one or more embodiments, the first composition comprises 0.5% to 5% by weight of the first polymer, based on the total weight of the first composition.
[0039] In some embodiments, the first composition comprises 80 wt% to 95 wt% PET as the first thermoplastic and 5 wt% to 20 wt% COC as the first polymer, based on the total weight of the first composition, and the second composition comprises 80 wt% to 100 wt% PET as the second thermoplastic and 0 wt% to 20 wt% COC as the second polymer, based on the total weight of the second composition.
[0040] In an embodiment of the biaxially oriented multilayer film, the first composition comprises 80% to 95% by weight of PTE as the first thermoplastic and 20% to 5% by weight of PBT as the first polymer, based on the total weight of the first composition, and the second composition comprises 80% to 100% by weight of PET as the second thermoplastic and 0% to 20% by weight of PBT as the second polymer, based on the total weight of the second composition. In some embodiments, the first composition comprises 85% to 95% by weight of PTE as the first thermoplastic and 15% to 5% by weight of PBT as the first polymer, or 90% to 95% by weight of PET as the first thermoplastic and 10% to 5% by weight of PBT as the first polymer, based on the total weight of the first composition. In various embodiments, the second composition comprises 90% to 100% by weight of PET as the second thermoplastic and 0% to 10% by weight of PBT as the second polymer, based on the total weight of the second composition.
[0041] In one or more embodiments, the biaxially oriented multilayer film has a bulk haze of 20% or less as measured by ASTM D 1003. The term "bulk haze" refers to the percentage of incident incandescent light transmitted through the film that is deflected or scattered more than 2.5 degrees from the direction of the incident light, whereas the term "light transmittance" refers to the percentage of incident light that passes through the film. The bulk haze of the biaxially oriented multilayer film may be measured with a spectrophotometer or a transmittance meter using ASTM method D 1003. In one or more embodiments, the bulk of the biaxially oriented multilayer film is 20% or less. In other embodiments, the haze is 18% or less, 15% or less, 12% or less, 10% or less, 8% or less, 5% or less, 3% or less, or 2% or less.
[0042] Biaxially oriented multilayer films contain intralayer voids within some of the individual layers in the stack. The intralayer voids in the biaxially oriented multilayer films include a first polymer that is immiscible with the first thermoplastic. The first polymer is immiscible with the first thermoplastic, thus forming a void within the thermoplastic polymer, where no thermoplastic polymer is present. The voids formed from the first polymer that is immiscible with the first thermoplastic become intralayer voids once the desired number of units A-B are formed. An intralayer void is a void that is limited to a single layer, such as the first layer A or the second layer B, or a single unit A-B.
[0043] In one or more embodiments of the biaxially oriented multilayer film, the intralayer void has a height greater than 0 and less than 0.4 μm. In some embodiments, the intralayer void has a height greater than 0 and less than 0.3 μm. When the intralayer void height is less than the wavelength range of visible light, the biaxially oriented multilayer film is believed to have less bulk haze and therefore a higher visible light transmittance than when the intralayer void height is greater than the wavelength range of visible light.
[0044] In one or more embodiments of the biaxially oriented multilayer film, the intralayer voids have a width-to-height aspect ratio of 20:1 to 500:1. In some embodiments, the intralayer voids have a width-to-height aspect ratio of 100:1 to 500:1. In further embodiments, the intralayer voids have a width-to-height aspect ratio of 250:1 to 500:1.
[0045] Figure 6 is an SEM micrograph of a multilayer film produced as a comparative example. The comparative example in Figure 6 is a monolayer film containing an immiscible polymer and a thermoplastic. The immiscible polymer forms voids in the thermoplastic. The voids in the comparative example have a height of more than 0.4 μm.
[0046] In one or more embodiments, the stack comprises multiple units (A-B) n where n represents the number of layers of A-B units. In some embodiments, (A-B) nThe subscript n is 50 or greater. In some embodiments, n is 55 to 600, 100 to 550, or 200 to 550. For example, (A-B) n where subscript n is 50 and there is only a first layer A and a second layer B in unit AB, then the stack includes 100 individual layers, where there is a repeating pattern of ABAB. In one or more embodiments, unit AB includes three layers, and such a stack has a repeating pattern of ACB, AAB, or ABB, where C is a third thermoplastic.
[0047] In one or more embodiments, at 260° C., the first composition has a first melt viscosity η1 and the second composition has a second melt viscosity η2, where |η1-η2| / η1 is greater than 0 to less than or equal to 0.2. In some embodiments, |η1-η2| / η1 is greater than 0 to 0.10, 0.01 to 0.1, 0.01 to 0.05, or 0.001 to 0.02. Wide interlayer variations in viscosity are known to destabilize laminar flow in multilayer systems. Flow instabilities can result in poor cross- or longitudinal thickness profiles in typical filming processes. Proper management of the viscosity profile is required to maintain film flatness within the multilayering process.
[0048] Without intending to be bound by any particular theory, it is believed that two polymers or two blends of polymers undergo typical extrusion melt conditions and are heated to approximately 10 to 100 s -1It is believed that there should be a relatively small difference in melt viscosity, such as a relative viscosity of 5% at a reasonable shear rate of 1000 nm, to create a biaxially oriented multilayer film with low density and low haze. The relatively small difference in viscosity limits the mixing of layers when the polymer or polymer blend is in a molten state (e.g., the polymer temperature is higher than the melt temperature of the polymer or polymer blend). The relatively small difference in viscosity allows the two polymers or polymer blends to be split and stacked to form a stack of A-B units. Splitting and stacking can be done multiple times to form 16, 32, 64, 128, 256, 512, or 1024 individual layers of A-B repeating layers. Once the desired number of layers is reached, the melt is forced through an extrusion die, cast onto water-cooled rollers, wrapped around a rotating core, or taken on for further processing as a thick plastic film. Materials with more than 5% melt viscosity difference at similar melt temperatures may exhibit rheological stresses between individual submicron layers. The stress can distort and distress the void structure, causing agglomerates to form, thereby increasing the bulk haze of the film.
[0049] There are various methods for producing multilayer films. One example of a method for forming a multilayer film involves combining two separate melt streams to form a bilayer system. The bilayer system passes through a feedblock that splits the bilayer system perpendicular to the stacking plane. The split bilayer system is guided apart vertically and passes through a die where it is flattened and stacked on top of each other. This effectively doubles the number of alternating layers. Multiple feedblocks can be added in series, doubling the amount of layers each time a layer passes through one of them. Examples of this technology can be found in U.S. Pat. Nos. 3,557,265, 3,565,985, 3,759,647, 5,380,479, 3,328,003, 3,565,985, 3,479,425, and U.S. Patent Publication No. 2012 / 0288696.
[0050] All numerical ranges in the present disclosure, e.g., "1 to 10," should be understood as disclosing, as separate embodiments, every individual value within the range, as well as every subrange within the range. For example, the range "1 to 10" discloses, as separate embodiments, every individual value from 1 to 10, inclusive, 1 and 10, as well as subranges including, but not limited to, "5 to 10," "2 to 8," "5 to 8," and "3 to 9." EXAMPLES
[0051] It should be understood that Examples 1-7 are provided to illustrate embodiments described in this disclosure and are not intended to limit the scope of this disclosure or its appended claims. Examples 1-3 were produced by Method A, with each example having a different number of layers. In Method A, the films produced had A / B / A / B layers, where Layer A was PET and Layer B was PET / COC. Examples 4-6 were produced by Method B, with each example having a different number of A / B / A / B layers. In Method B, films were produced, where Layer A was PET / COC and Layer B was PET / COC. Example 7 was produced by Method C, with the film produced from Method C including a PET layer and a PTE / PBT layer.
[0052] Method A - Preparation of Examples 1-3 Multilayer thermoplastic films were produced by extruding a stack of A-B units of thermoplastic material. The thermoplastic material included a layer of PET and another layer of PET mixed with 10 wt% COC. After casting, the film was oriented in a Karo IV off-line film stretcher. This equipment is commercially available from Brukner Incorporated. The polyester resin selected had an intrinsic viscosity (IV) of 0.69 and was purchased commercially from Polyquest Industries as grade PCQ69. The COC selected was manufactured by Topas as grade 5013-F. Prior to extrusion, the PET resin was dried to remove moisture in order to maintain melt strength for extrusion. Although not required, polyethylene capping layers were extruded on both sides of the doublet stack to enhance melt flow in the tests.
[0053] The formed multilayer film is then stretched in both major axes via one of two methods: off-line or in-line stretching and orientation. For small scale off-line stretching, such methods are convenient for testing and evaluating new film formulations. In this case, the squares of film can be oriented simultaneously or sequentially by a system of mechanically linked clamps in an oven (as in the Bruckner Karo IV test machine).
[0054] Online Stretching: First, the cast film is heated and stretched in the machine direction by a pair of rollers. Typically, the film is held or pinched under pressure between the rollers. The second set of rollers rotates 2-4 times faster than the first set of rollers, so the cast film is drawn into a longer, thinner web that moves at a faster speed. The film is then moved to a static oven, where pairs of clips attached to moving chains continuously capture the edges of the film and force them apart after a short heating period. As the chains are forced apart, the film's width increases by a factor of 3-4, and the film thins by the same amount. This biaxial stretching dramatically increases the strength of the film, typically via strain-induced crystallization of the polymeric material within the film.
[0055] The layered film of Example 1 was produced by coextrusion as described in Method A, followed by nine square mixing elements.
[0056] The layered film of Example 2 was produced by coextrusion as described in Method A, followed by eight square mixing elements.
[0057] The layered film of Example 3 was produced by coextrusion as described in Method A, followed by seven square mixing elements.
[0058] Method B - Preparation of Examples 4 to 6 In producing the multilayer films of Examples 4-6, multilayer thermoplastic films were produced by extruding a doublet stack of thermoplastic materials consisting of a layer of PET mixed with 8% COC and another layer of PET mixed with 10% COC by weight. After casting, the film was oriented in a Karo IV off-line film stretcher. The polyester resin selected had an intrinsic viscosity (IV) of 0.69 and was purchased commercially from Polyquest Industries, Inc. as grade PCQ69. The COC selected was manufactured by Topas, Inc. as grade 5013-F. Prior to extrusion, the PET resin was dried to remove moisture in order to maintain melt strength for extrusion. Although not required, a polyethylene capping layer was extruded on both sides of the doublet stack to enhance melt flow in testing.
[0059] The layered film of Example 4 was produced by coextrusion as described in Method B, followed by nine square mixing elements.
[0060] The layered film of Example 5 was produced by coextrusion as described in Method B, followed by eight square mixing elements.
[0061] The layered film of Example 6 was produced by coextrusion as described in Method B, followed by seven square mixing elements.
[0062] Method C - Preparation of Example 7 The multilayer film of Example 7 was produced by extruding a doublet stack of thermoplastic materials: a layer of PET and another layer of PET mixed with 10 wt% polybutylene terephthalate (PBT). The PBT selected had a melt viscosity similar to that of PET and was supplied by DuPont. After molding, the film was oriented in a Karo IV off-line film stretcher. The polyester resin selected had an intrinsic viscosity (IV) of 0.69 and was purchased commercially as grade PCQ69 from Polyquest Industries. Prior to extrusion, the PET resin was dried to remove moisture in order to maintain melt strength for extrusion. Although not required, a polyethylene capping layer was extruded on both sides of the doublet stack to enhance melt flow in testing.
[0063] The layered film of Example 7 was produced by coextrusion by Method C, followed by eight square mixing elements.
[0064] Comparative Example C1 The multilayer film of Comparative Example C1 was produced by extruding a doublet stack of thermoplastic materials consisting of a layer of PET and another layer of PET mixed with 10 wt% PBT and calcium carbonate. PBT / calcium carbonate masterbatches are commercially available from a number of sources. After casting, the film was oriented in a Karo IV off-line film stretcher. The polyester resin selected had an intrinsic viscosity (IV) of 0.69 and was purchased commercially as grade PCQ69 from Polyquest Industries, Inc. Prior to extrusion, the PET resin was dried to remove moisture in order to maintain melt strength for extrusion. Although not required, polyethylene capping layers were extruded on both sides of the doublet stack to enhance melt flow in testing.
[0065] The film of Comparative Example C1 was produced by coextrusion followed by eight square mixing elements.
[0066] Comparative Example C2 Multilayer thermoplastic films were produced by extruding a doublet stack of thermoplastic materials consisting of a layer of PET and another layer of PET mixed with 10% by weight polypropylene. A series of square mixers followed the melt stream and forced the resin material onto chilled rolls. After casting, the film was oriented in a Karo IV off-line film stretcher. The polyester resin selected had an intrinsic viscosity (IV) of 0.69 and was purchased commercially as grade PCQ69 from Polyquest Industries, Inc. The PP selected (Pinnacle 1703) was. Prior to extrusion, the PET resin was dried to remove moisture to maintain melt strength for extrusion. Although not required, polyethylene capping layers were extruded on both sides of the doublet stack to aid in drawing the polymer melt out of the die.
[0067] Comparative Example C2 layer film was produced by coextrusion as described in E, followed by seven square mixing elements. Very high haze was observed in this sample. SEM analysis of the layer structure shows that the PP resin crosses the interfacial boundaries of the 254 multilayer stack, resulting in the circular voids required for high clarity at low density.
[0068] Comparative Example C3 A monolayer film containing 92% PTE with an IV of 0.62 was mixed with 8% COC by weight. The extruded and quenched material was oriented in the MD and TD by conventional methods such as those described in US9580798 and US10131122. High haze and high opacity were observed along with a decrease in film density.
[0069] Comparative example C4 A tri-layer film containing virgin PET was produced according to conventional methods described in US Pat. Nos. 9,580,798 and 10,131,122.
[0070] The properties of inventive examples 1-7 and comparative examples C1-C4 are reported in Table 1.
[0071] [Table 1]
[0072] The multilayer films of Examples 1-7 had at least 512 layers and a bulk haze of less than 20. 2 The multilayer film of Comparative Example C1 had a density of less than 1.17 g / cm 2 Although the multilayer film had a low density of 0.86 g / cm, its bulk haze was 55.3 and the film was opaque. Similarly, the multilayer film of Comparative Example C2 had a low density of 0.86 g / cm 2 However, it had a large bulk haze of 92.2, which was larger than the bulk haze of the multilayer film of Comparative Example C1.
[0073] The film of Comparative Example C3 was a monolayer film. It had a low density of 1.23 g / cm 2 The bulk haze of the monolayer film was measured to be high, at 86. In contrast, the multilayer film of Comparative Example C4, which is a three-layer film, had good optical quality with a bulk haze of 4, but the density of the film was 1.40 g / cm 2 Larger, specifically 1.41 g / cm 2 It was.
[0074] Measurement method Haze can be measured as known in the art, such as using ASTM D1003 or an equivalent technique. Density can be measured by any of the well-known methods, such as ASTM D792, or using helium or nitrogen pycnometry.
Claims
1. A biaxially oriented multilayer film, comprising: A stack of n layer units A-B (A-B) n A stack (A-B) of n layer units A-B, where n is 32 or more, and each layer unit A-B has an individual layer including a first layer A and a second layer B overlying the first layer A. n and, an intralayer void within a portion of the individual layers in the stack, the intralayer void having a width-to-height aspect ratio of 20:1 to 500:1; the first layer of the layer unit has a first composition, the first composition comprising a first thermoplastic and a first polymer; the second layer of the layer unit has a second composition, the second composition comprising a second thermoplastic; the second thermoplastic is the same as or different from the first thermoplastic; the first composition has a first melt viscosity η 1 at 260° C.; the second composition has a second melt viscosity η 2 at 260° C.; Here, |η 1 - η 2 | / η 1 is greater than 0 and is equal to or less than 0.2; and The biaxially oriented multilayer film has a bulk haze of less than 20 as measured by ASTM D1003. Biaxially oriented multilayer film.
2. |η 1 -η 2 | / η 1 The biaxially oriented multilayer film of claim 1 , wherein is greater than 0 to 0.
10.
3. 3. The biaxially oriented multilayer film of claim 1 or 2, wherein the first composition comprises from greater than 0 to approximately 10 weight percent of a first polymer, based on the total weight of the first composition.
4. The biaxially oriented multilayer film of any one of claims 1 to 3, comprising at least 250 layer units.
5. The biaxially oriented multilayer film of any one of claims 1 to 4, comprising at least 500 layer units.
6. The biaxially oriented multilayer film of any one of claims 1 to 5, comprising at least 1000 layer units.
7. The biaxially oriented multilayer film of any one of claims 1 to 6, wherein the first thermoplastic material is polyethylene terephthalate (PET).
8. The biaxially oriented multilayer film according to any one of claims 1 to 7, wherein the first thermoplastic and the second thermoplastic are PET.
9. The biaxially oriented multilayer film of any one of claims 1 to 8, wherein the first polymer comprises cycloolefin copolymer (COC) or polybutylene terephthalate (PBT).
10. The biaxially oriented multilayer film of any one of claims 1 to 9, wherein the second composition further comprises a second polymer.
11. The first composition comprises, based on the total weight of the first composition, 80 wt. % to 95 wt. % of PET as the first thermoplastic material and 5 wt. % to 20 wt. % of COC as the first polymer; and 11. The biaxially oriented multilayer film of claim 10, wherein the second composition comprises, based on the total weight of the second composition, 80 to 100% by weight of PET as the second thermoplastic material and 0 to 20% by weight of COC as the second polymer.
12. the first composition comprises 80 wt% to 95 wt% PET as the first thermoplastic and 5 wt% to 20 wt% PBT as the first polymer, based on the total weight of the first composition; and 11. The biaxially oriented multilayer film of claim 10, wherein the second composition comprises, based on the total weight of the second composition, 80 to 100% by weight of PET as the second thermoplastic material and 0 to 20% by weight of PBT as the second polymer.
13. The biaxially oriented multilayer film of any one of claims 1 to 12, wherein the intralayer voids have a height of less than 500 nm.
14. A biaxially oriented multilayer film as claimed in any one of claims 1 to 13, wherein the intralayer voids have a height of less than 400 nm.
Citation Information
Patent Citations
Polyester film
JP2018030901A